A pharmacogenetic study of cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex 1 (VKORCl) / Immaculate Mbongo Langmia - Mbongo Langmia, Immaculate (2011)
A fast and reliable genotyping method for detection of single nucleotide polymorphisms (SNPs) of VKORCl was developed. PCR methods used for detection of CYP2C9 (CYP2C9*1 and CYP2C9*3) SNPs were previously developed in house. The optimized nested allele specific polymerase chain reaction (AS-PCR) method was used to investigate the influence of VKORCl and CYP2C9 in warfarin therapy. Genotype frequencies among warfarin patients were explored and specific clinical parameters of the patients was correlated with VKORCl and CYP2C9 genotypes. A total of 163 (50% of Malay and the remaining Chinese) warfarin patients were recruited after written informed consent. The patients were monitored for a period of six month and their medical records reviewed. Four SNPs including 2 for VKORCl (G-1639A (rs9923231) in the 5 flanking region and C1173T (rs9934438) in exon 2) and 2 for CYP2C9 (CYP2C9*! and CYP2C9*3) were examined in this study. For VKORCl-1639G/A (rs992323i;, three genotypes were detected, A-1639A, G-1629A and G-1639G. For VKORCl-1173C/T (rs9934438) three genotypes were also detected, T1173T, C1173T and C1173C respectively. The variant alleles A-1639A and T1173T were the most frequent. When grouped into the different races, the two genotypes were higher in the Chinese patients than the Malay. The frequency of the A-1639A genotype was 76.5% in the Chinese in contrast to 53.7% in the Malay. The T1173T genotype existed in 76.5 per 100 Chinese patients compared to 45.3 per 100 Malay patients. CYP2C9*1/*1 was detected in 93.3% of the patients and the remaining were having CYP2C9*l/*3 (6.7%). Following analysis results, variants of VKORCl and CYP2C9 were associated with variability in warfarin dose. Patients with the T1173T genotype required a mean dose of 3.03 mg (SD 1.1) opposed to 4.4 mg (SD 1.4) and 5.6 mg (SD 2.5) for patients with the C1173T and C1173C respectively. Patients with the CYP2C9*l/*3 required significantly lower dose to achieve therapeutic INR levels. Patients with the wild type genotype required 3.5 mg (SD 1.4) of warfarin compared to 2.5 (SD 1.1) mg for patients with CYP2C9*l/*3 to maintain the same INR level of 2.0 to 4.0. This clearly demands for individualized warfarin therapy in the Malaysian population and it can be achieved by genotyping of CYP2C9 and VKORCl. There was a poor relationship between INR values and the amount of doses given to the patients. In terms of environmental factors, analysis results showed that age was a significant predictor but weight and height were not. There was no significant difference in dose between male (3.6 mg SD 1.29) and female (3.4 mg SD 1.54). Patients with the variant genotype (A-1639A and T1173T) experienced the highest bleeding rate. Thirty five (35) patients experienced bleeding during the treatment period.